Komunikasi Persuasif Argumentatif Perspektif Alquran: Studi terhadap Dialog Ibrahim dengan Penganut Paganisme - Ahmad Rizali Fahmi (Jisab, 2023)
The success of da'wah is directly proportional to the success of the applied communication. One form of Islam's great concern for communication is that Islam provides an explanation of its rules and ethics. One of the successes of the preaching of the prophets was by applying communication that is persuasive and seducing known as persuasive, but it also applies communication that shows a series of facts and evidence in such a way that is called argumentation ability so that it is called persuasive argumentative communication. Among the argumentative persuasive communications contained in the Qur'an is the dialogue between the Prophet Abraham and adherents of paganism. In this dialogue, there are arguments about the true nature of God that must be worshiped and glorified. Argumentative persuasive communication provides a solution for a preacher who is a communicator in packaging his communication so that the object of his da'wah follows what is conveyed regarding his da'wah. By using persuasive communication techniques that emphasize the psychological and sociological functions contained in the communicant and with argumentation techniques that optimize the function of dialogue wisely with the interlocutor, it will make the da'wah message conveyed able to change the views, attitudes and behavior of the da'wah object or the communicant.